Dampak penerapan teknik konservasi Tanah dilahan kering terhadap Sifat fisik tanah=Impact of Soil Conservation Techniques Practices in Uplands Area on Soil Physical Properties - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT The uplands area for agricultural development in Special Territory of Yogyakarta Province (DIY) decreases due to increasing land demands for non agricultural sector. On the other hand, part of the uplands area were located in the hilly formation with steep slope (>15%) had been degraded lands and was declined in physical and chemical soil properties. The main problems of degraded uplands in DIY among others were due to the erosion rate was more than the soil formation rate, the lands utilization which was not the land capability, and poor management in soil conservation practices. To improve the degraded uplands and soil conservation techniques practices (as mechanical and vegetatives methods) had been carried out in the three representative uplands location, i.e. in Karangasem, Gunung Kidul District (MAII) on the Lithicllstropepts